Student Attitude and Readiness Towards Virtual Learning for Practical Classes of Building Construction Program - Ariffin, Arihasnida (Research and Innovation in Technical and Vocational Education and Training, 2023)
This study aims to identify attitudes, readiness and identify attitudes and readiness based on students' gender differences in virtual practical learning. The study involved 117 students ranging from Cohort 9 to Cohort 13 students. A pilot study was conducted on 30 students to determine the validity and reliability of the research instruments and the results of the pilot study, the alpha Cronbach test value in section B (0.859) and section C (0.875) were at a high level and could be used for actual study. This study is in the form of survey using quantitative approach through instrument questionnaire. Average mean score value for student attitude is at moderate level towards virtual practical learning. Meanwhile, the mean score average for student readiness is at a high level. From a different point of view, there are significant differences in attitudes based on student gender while for readiness there is no significant difference based on student gender aspect. This study suggests that the faculty and lecturers are sensitive to the factors that influence the attitude and readiness of students of the Building Construction program and to try to improve the problems that are the drivers of practical learning issues in virtual.